2018
DOI: 10.1016/j.jid.2017.07.851
|View full text |Cite
|
Sign up to set email alerts
|

RNA Aptamer Delivery through Intact Human Skin

Abstract: It is generally recognized that only relatively small molecular weight (typically < ∼ 500 Da) drugs can effectively permeate through intact stratum corneum. Here, we challenge this orthodoxy using a 62-nucleotide (molecular weight = 20,395 Da) RNA-based aptamer, highly specific to the human IL-23 cytokine, with picomolar activity. Results demonstrate penetration of the aptamer into freshly excised human skin using two different fluorescent labels. A dual hybridization assay quantified aptamer from the epidermi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 21 publications
(22 reference statements)
0
13
0
Order By: Relevance
“…The improved half‐life of aptamers in vivo is suggestive of future clinical application as molecular imaging agents . Of note, aptamers themselves can be used as therapeutics in blood clotting, or local treatment, or inducing antitumor effect . Furthermore, aptamer‐mediated delivery systems have been broadly applied in cancer therapies, including aptamer‐drug conjugates, aptamer‐nanoparticle/polymer‐drug delivery system, and aptamer‐mediated cancer nucleic acid therapy .…”
Section: Aptamer Emerges As a Prominent Targeting Ligand For Nanodelimentioning
confidence: 99%
“…The improved half‐life of aptamers in vivo is suggestive of future clinical application as molecular imaging agents . Of note, aptamers themselves can be used as therapeutics in blood clotting, or local treatment, or inducing antitumor effect . Furthermore, aptamer‐mediated delivery systems have been broadly applied in cancer therapies, including aptamer‐drug conjugates, aptamer‐nanoparticle/polymer‐drug delivery system, and aptamer‐mediated cancer nucleic acid therapy .…”
Section: Aptamer Emerges As a Prominent Targeting Ligand For Nanodelimentioning
confidence: 99%
“…Theoretically, only small molecules with certain characteristics are able to penetrate tissues. However, it has been reported that even aptamers (~23.5 KDa) are able to penetrate tissues or even being translocated to the cells (Lenn et al 2018; Wang, Ding, and Zhou 2019). Our M1 aptamer could be further tested for cell permeability in appropriate laboratory facilities that could unlock novel approaches for in vivo visualization of TDF in the cell.…”
Section: Discussionmentioning
confidence: 99%
“…The use of topical siRNA is limited because of its low permeability through the epidermis, its high molecular weight, its negative charge, and its susceptibility to degradation by endogenous enzymes [62][63][64]. For this reason, efforts in topical siRNA delivery are being focused on chemical methods to prepared carrier molecules able to mask siRNA-negative charges, compress the siRNA molecule to make it smaller, and protect siRNA from degradation as well as the use of physical methods [65].…”
Section: Gene Therapy In Alopeciamentioning
confidence: 99%